"I Had Let Everyone, Including Myself, Down": Illuminating the Self-Forgiveness Process Among Female College Students. Issue 2 (3rd April 2019) - Carlos Chavez, Fiorella L.; Wolford, Sarah N.; Kimmes, Jonathan G.; May, Ross W.; Fincham, Frank D.
Abstract: The self-forgiveness process may be considered emotionally taxing among college students. The current study explored college students' past intrapersonal transgressions (n = 88) through two outcomes (able or unable to forgive oneself). Using NVivo 11 Pro software, thematic analyses revealed the most common situational circumstances and internal emotional determinants that were embedded in these contexts. Findings highlight the need to revise the existing self-forgiveness model to include experiences related to intrapersonal transgressions. Clinical implications include relevant intervention strategies to engage in the self-forgiveness process of an intrapersonal transgression among emerging adults. Directions for theory development are discussed.